Inﬂuence of hand movement on skin deformation: a therapeutic glove design perspective - Nasir, Siti Hana; Troynikov, Olga (Elsevier, 2017)
The ﬁt of a therapeutic glove directly inﬂuences the hand function of the wearer as well as wear comfort. Static and dynamic hand dimensions and characteristics must be considered when designing a glove, as signiﬁcant changes in hand shape, size, and skin surface morphology result from hand movements. The aim of this study is to investigate the skin relaxed-strain ratio at the dorsal side of the hand and its relationship to skin deformation behaviour during hand movements. The point cloud raw data of the right hands of 13 female participants (40e65 years, size M) were recorded using a 3D INFOOT scanner in three different hand postures. Twenty-two measurements of skin relaxed-strain ratios in each posture were calculated, and differences between them were identiﬁed using the Kruskal-Wallis H test. The results demonstrate that different hand postures cause substantial changes in hand geometry, especially in the metacarpal region. The ﬁndings of this study are valuable for the construction of functional tight-ﬁtting therapeutic gloves with optimal ﬁt, performance, and comfort.